WOMENS LEADERSHIP IN ISLAM: A HISTORICAL PERSPECTIVE OF A HADITH - Bakri, Syamsul (UIN Raden Mas Said Surakarta, 2020)
This paper aims to describe woman’s leadership in Islam. Woman’s leadership had become considerable polemic in Islamic history. The data source of this qualitative research was taken from books of hadith. The data was analyzed using the hermeneutical Takhrij method and historical approach. A conclusion drawn from this study is that the woman’s leadership prohibition originally was referred from hadith narrated by Abu Bakrah as the common link. He had interpreted the meaning of hadith from his cognizance. It was influenced by his philosophy of cosmology and culture at that time, which cannot be said to represent Islam. In critical studies, hadith has a temporal and conditional meaning. The prohibition for women’s leadership occurred because many ulama interpret the misogynist hadith textually, instead of historically. This historical approach to misogynist hadith has led to the conclusion that there is nothing wrong with women’s leadership in government as long as they have the capacity, knowledge, and skills. The psycho-historical approach at the time of the Prophet Muhammad and the socio-cultural conditions that developed during the era increasingly showed that the hadith was not an absolute prohibition for a woman to lead a government.